Challenges in communicating climate change. Treatment in the Uruguayan press. - Arzuaga-Williams, Mónica (2024)
Climate change is a current problem that challenges public communication due to its complex scientific nature. These local socio-political, discursive, cultural and demographic interrelations interfere with public communication due to particular emotional conditions that intervene in the perception and interpretation of the problem. The framing of the news by journalists, when it addresses the specific conditions for communicating about climate change, can influence interest and understanding of the topic. To describe the treatment carried out by the press in Uruguay, exploratory research with content analysis was carried out on a sample of articles published in 2023 in which the applied frameworks were identified and analysed. The results show that the treatment of climate change is related to the journalistic model and practices of the media and not to their ideological orientation. The frameworks applied to present content on climate change in the articles do not respond to the difficulties that the phenomenon implies for public communication.